Cinnamaldehyde and related phenylpropanoids, natural repellents, and insecticides against Sitophilus zeamais (Motsch.). A chemical structure-bioactivity relationship - Zaio, Yésica Paola (2018)
Insecticidal activity and repellent effects on adults of Sitophiluszeamais of 12 cinnamaldehyde-related compounds was evaluated by contacttoxicity bioassays and a two-choice olfactometer, respectively. To determinenon-toxicity in mammals, additionally, body weight, serum biochemical profiles,liver weight, physiological parameters, sperm motility and histopathological data were obtained as complementary information in C57BL/6 mice, treated with the best natural compound. RESULTS: Based on 24h LC95 and LC50 values, alpha-methyl-cinnamaldehydeand cinnamaldehyde, respectively, exhibited better insecticidal activity than the other compounds. The best repellent effect was observed with alpha-bromocinnamaldehyde, which even repelled at the lowest concentration studied (0.28µM). The evaluation of a quantitative structure-activity relationship showed a linear relationship between the LC50 values for adult weevil toxicity and dipolo with Q (difference between orbital electronegativity carbon 1 and orbital electronegativity carbon 3 of the molecule) values in cinnamaldehyde-related compounds. In addition, the polar surface and Log P descriptors also revealed a linear relationship with the S. zeamais repellent effect for cinnamaldehyde analogues. Besides, cinnamaldehyde did not show toxicity in the parameters evaluated in mice.CONCLUSION: From the phenylpropanoid components studied, the naturalcompound which had the best insecticidal and repellent activity against S.zeamais was cinnamaldehyde and presented no mammalian toxicity.